Experimental multi-level seismic performance assessment of 3D RC frame designed for damage avoidance. - Bradley, Brendon A. (Earthquake engineering & structural dynamics.)
This paper experimentally investigates the application of damage avoidance design (DAD) philosophy to moment resisting frames with particular emphasis on detailing of rocking interfaces. An 80 percent scale three dimensional rocking beam-column joint sub-assembly designed and detailed based on damage avoidance principles is constructed and tested. Incremental dynamic analysis is used for selecting ground motion records to be applied to the sub-assembly for conducting a multi-level seismic performance assessment (MSPA). Analyses are conducted to obtain displacement demands due to the selected near and medium field ground motions that represent different levels of seismic hazard. Thus, predicted displacement time histories are applied to the sub-assembly for conducting quasi-earthquake displacement tests. The sub-assembly performed well reaching drifts up to 4.7 percent with only minor spalling occuring at rocking beam interfaces and minor flexural cracks in beams. Yielding of post tensioning threaded bars occured, but the sub-assembly did not collapse. The externally attached energy dissipators provided large hysteretic dissipation during large drift cycles. The sub-assembly satisfied all three seismic performance requirements, thereby verifying the superior performance of the DAD philosophy.